Study of Attractive Nonlinearity by 1-D Nonlinear Schrödinger Equation in the BoseâEinstein Condensate - Rahman, ML; Haque, Y; Das, SK; Hossain, MM; Rashid, MH (Journal of Bangladesh Academy of Sciences, 2009)
The work represents and investigates the stationary solutions of the one-dimensional Non-linear Schrödinger Equation (NLSE), for attractive non-linearity, in the Bose-Einstein condensates (BEC) under the box boundary condition and calculates the characteristics of internal modes of bright solitons (eigen modes of small perturbation of the condensate). DOI: 10.3329/jbas.v33i1.2953 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 87-98, 2009